The Role and Effectivity of Face Mask in Preventing Transmission of Coronavirus Disease 2019 (COVID-19) - Cindy Gustavia Dwirusman (Yayasan Pendidikan Medika Indonesia, 2020)
Coronavirus disease 2019 (COVID-19) is a respiratory disease with an etiology of coronavirus (SARS-CoV-2). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was found in pneumonic patient in Wuhan City, Hubei Province, China in December 2019. 2019-nCoV infection causes various clinical manifestations such as fever, dry cough, dyspnoe, chest pain, fatigue and myalgia. Health and safety protocols plays a vital role in preventing COVID-19 transmission. Face mask is an example of preventive measure for coronavirus disease 2019. there are various types of mask made of different materials with different functions such as N95 mask, surgical or medical mask, and mask made of cloth. Every type of mask has its own effectivity as well as filtration capabilities. The effectivity of a mask is affected by several factors such as type of material, pandemic usage, healthcare workers and public usage, and other safety measures including hand washing, social distancing and the use of other Personal Protective Equipments (PPE). Acknowledging filtration effectivity of each mask is expected to increase the accurate of of mask to reduce the risk of COVID-19 transmission.